Risk Factors for Leprosy in All Health Centers at the Bau-Bau City - Sriningsih, Cun; Sunarsih, Sunarsih; Rahmawati, Rahmawati (Waluya The International Science of Health Journal, 2023)
Backgrounds: Leprosy is spreading throughout the world, with most cases occurring in tropical and subtropical regions. For the last 3 (three) years until 2021 of all Regencies / Cities in Southeast Sulawesi, the Regency / City with the highest prevalence of leprosy cases is Bau-Bau City. This study aims to analyze the risk factors for leprosy in all health centers in Bau-Bau City. Methods:The type of research used in this study is quantitative research, using the Case Control Study research design.The case population in this study was 47 people. The sample of research cases was 41 people and with a ratio of 1: 1, so that the total sample amounted to 82 people. In this study, the research sampling technique used Simple Random Sampling.Analysis of the research data was carried out descriptively and inferentially using the Odd Ratio test. Results: The results showed that education (OR=3.109) and personal hygiene (OR=4,844). Conclusion: Education and personal hygiene are risk factors ofthe incidence of leprosy in all health centers in Bau-Bau city.